2021
DOI: 10.1016/j.heliyon.2021.e07467
|View full text |Cite
|
Sign up to set email alerts
|

Developing the amazing photocatalyst of ZnAg2GeSe4, ZnAg2Ge0.93Fe0.07Se4 and ZnAg2Ge0.86Fe0.14Se4 through the computational explorations by four DFT functionals

Abstract: For developing the stannite type quarterly crystal photocatalyst, the electronic structure and optical properties of ZnAg 2 GeSe 4 , ZnAg 2 Ge 0.93 Fe 0.07 Se 4 and ZnAg 2 Ge 0.86 Fe 0.14 Se 4 were calculated and compared with the parent stannite type quarterly crystal, ZnAg 2 GeS 4 . First of all, the four functionals, such as GGA with PBE, GGA with RPBE, GGA with WC and LDA with CA-PZ functionals were used for primary screening of electronic band structure and structural geometry for ZnAg 2 GeS 4 while the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 44 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…Further, it is noteworthy that the electrical conductivity of a material arises owing to the flow of electrons from the conduction band or holes to the valence bands. The transfer of electron density from one group to another group indicates the separation of charge during electronic transition. To elucidate the role of component MOs and their related energy values, density of states (DOS) plots are solved. From DOS diagram (Figure ), the difference between band edges are well documented.…”
Section: Resultsmentioning
confidence: 99%
“…Further, it is noteworthy that the electrical conductivity of a material arises owing to the flow of electrons from the conduction band or holes to the valence bands. The transfer of electron density from one group to another group indicates the separation of charge during electronic transition. To elucidate the role of component MOs and their related energy values, density of states (DOS) plots are solved. From DOS diagram (Figure ), the difference between band edges are well documented.…”
Section: Resultsmentioning
confidence: 99%
“…The real part (σ r ) and imaginary part (σ i ) of the dielectric function ε (ω) are linked through the following expressions in equation (3) and equation (4) : here, the conductivity, as described by σ i = ωε 2 (ω), is directly proportional to the real and imaginary components of the dielectric constant. In the context of active photocatalysts, it's imperative that the band gap between the valence and conduction bands remains less than 1.8 eV [ 45 ]. As depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, this research endeavors to conduct a comparative computational analysis, focusing on to dissect Ag 3 VO 4, Ag 2 CO 3, tetragonal Ag 3 VO 4 , and Ag 3 VO 4 as potential photocatalysts for wastewater treatment. To achieve this goal, computational tools were employed to design these crystals and conduct a comprehensive evaluation using five Density Functional Theory (DFT) functionals: Generalized Gradient Approximation (GGA) with Perdew Burke Ernzerhof (PBE), Generalized Gradient Approximation (GGA) with Revised Perdew Burke Ernzerhof functional (RPBE), Generalized Gradient Approximation (GGA) with Perdew-Berke-Ernzerhof for solids (PBEsol), Perdew-Wang-91 (PW 91 ), and Wu-Cohen (WC) [ [43] , [44] , [45] ], chosen for their effectiveness and accuracy compared to other DFT functionals [ 46 ]. The selection of the band gap concept as the focal point of this study is rooted in the profound correlation observed between a reduced band gap and the heightened photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Withal, it must be noted for optimization structure showing in Figures 1a to 1d which were taken after simulation GGA with RPBE which has been considered as the standard functional of DFT having heavy metal atoms in crystal. But the GGA with PBE, which has estimated the most accurate and acceptable DFT functional for calculating the electronic structure of heavy metals containing crystals [30][31][32][33][34] shows very close magnitude of band gap.…”
Section: Geometry Of Optimized Structurementioning
confidence: 99%